Surgical Correction of Adult Congenital Penile Curvature: A Systematic Review. Issue 2 (5th January 2022) - Britton, Cameron J.; Jefferson, Francis A.; Findlay, Bridget L.; Sharma, Vidit; Hernandez, Jonathan Clavell; Levine, Laurence A.; Ziegelmann, Matthew J.
ABSTRACT: Background: Congenital penile curvature (CPC) is corrected surgically by various corporoplasty or tunica albuginea plication techniques, but the optimal surgical approach is not well-defined. Aim: To provide a comprehensive evaluation of the published literature pertaining to outcomes with penile plication and corporoplasty techniques for surgical management of CPC. To determine if plication or corporoplasty offers superior outcomes in surgical correction of CPC. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Checklist. The following databases were queried from inception to March 18, 2020 to search for studies describing surgical treatment of CPC: Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations and Daily, Ovid Embase, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews, and Scopus. Outcomes: Objective and subjective postoperative outcomes including penile straightening, shortening, penile sensory changes, and reoperation rates for both corporoplasty and tunica albuginea plication were summarized. Results: Fifty-five articles comprising 2, 956 patients with CPC who underwent a plication procedure (n = 1, 375) or corporoplasty (n = 1, 580) were included. The definition of "treatment success" varied widely and most often involved subjective patient reporting (22 studies; 40%) or objective assessment (15 studies; 27%). We considered curvature correction to be satisfactory if there was self-reported patient satisfaction or residual curvature after correction of <20˚. Reported rates of successful straightening ranged from 75 to 100% and 73 to 100% for plication and corporoplasty, respectively. A comprehensive and accurate assessment of surgical outcomes for CPC correction, such as satisfactory penile straightening, reoperation rates, glans sensory changes, and other complications was limited by significant inter-study heterogeneity with respect to the reporting of treatment outcomes. Clinical Implications: While both plication and corporoplasty appear to be safe and effective options in the treatment of CPC, definitive conclusions cannot be drawn with respect to treatment superiority due to low-quality study design, methodology flaws, and significant heterogeneity in reporting. Strength & Limitations: This report represents the most comprehensive review of CPC surgical management. However, there is a significant lack of standardization in the reporting of treatment outcomes for CPC, thereby limiting the reliability of the published data summarization encompassed by our review. Conclusion: Both plication and corporoplasty demonstrate high success rates and relatively low complication rates in the treatment of CPC, albeit with low-level evidence available in most research publications. Robust comparison of the surgical techniques used to correct CPC is limited by significant variation in reporting methods used in the literature.